Evaluation of equivalent dose to eye lens through dose equivalent Hp(3). (August 2019) - Marcantonini, Marta; Chiappiniello, Andrea; Beneventi, Sara; Reggioli, Valentina; Dipilato, Anna C.; Fulcheri, Christian P.L.; Iacco, Martina; Zucchetti, Claudio; Tarducci, Roberto
Highlights: Hp (0.07) does not underestimates equivalent dose to eye lens obtained by Hp (3). Hp (0.07) can be used instead of Hp (3) to evaluate Hlens in exposed workers. Equivalent dose to eye lens of the analyzed workers was always smaller than 3 mSv. Abstract: Purpose: Individual dosimetry allows to quantify doses from ionizing radiation of exposed workers. Scientific and epidemiological evidences highlight the need for adequate measures for a greater protection of the eye and a reduction in annual doses. ICRP Publication 103, illustrating the operational dose quantity Hp(d) for the individual monitoring, proposes a depth d = 3 mm for eye lens monitoring, indicating that even the Hp(0.07) can be used. In this study, it was investigated if there are differences in the evaluation of the equivalent dose to eye lens (Hlens ) using Hp(3) or Hp(0.07). Materials and methods: A slab phantom calibration was performed by an Accredited Calibration Laboratory in terms of Hp(3) and Hp(0.07) using ext-rad TLD-100 (LiF:Mg, Ti) dosimeters. Hp(0.07) and Hp(3) were measured for 26 exposed workers to assess Hlens . The measuring took place monthly in 2017 to obtain both semestral and annual doses. Results: Hlens (0.07) was always smaller than Hlens (3). However, the differences were not statistically significant (Mann-Whitney test, p > 0.05) for both semestral and annual doses. The percentage differences were 7 ± 3%, 6 ± 3% and 7 ± 2% for I semester, II semester and whole year, respectively. The mean underestimation index <10%, intra-class correlation coefficient >0.99, coefficient of variation <3% and the excellent correlation (R 2 ≈ 0.999) for both semestral and annual doses highlighted that Hp(0.07) can be used to evaluate Hlens instead of Hp(3). Conclusions: No statistical evidence was found that the use of Hp(0.07) underestimates the equivalent dose to eye lens obtained through Hp(3).